Вы находитесь на странице: 1из 3

MATH 2108 TEST 2 - SOLUTIONS

1:
cos2 n 1 1
0 < cos2 n 1 =) 0 < and lim 3n = 0:
e3n e3n n!1 e

cos2 n
Then lim = 0 by the squeeze theorem:
n!1 e3n

2.
ex 1 ex (ex + 1) ex (ex 1) 2ex
f (x) = ;x 1: f 0 (x) = = > 0, x 1:
ex + 1 (ex + 1)2 (ex + 1)2

So the sequence is increasing:

en 1
0< < 1; n 1: So the sequence is bounded:
en + 1

The sequence, being monotonic and bounded, is convergent.

3.
X
1 X
1
5k 1
5k 1 6 k
= is a geometric series (GS) with :
k=1 k=1
6k

1 5
…rst term a = and common ratio r = :
6 6

5
jrj = < 1 =) the GS converges.
6

a 1=6
Since the GS converges, its sum is S = = = 1:
1 r 1 5=6

1
4.
x2 x2 x2 x2
f (x) = xe ; f 0 (x) = e + xe ( 2x) = (1 2x2 )e < 0, x 1:

Thus f is nonnegative, continuous, and decreasing for x 1.

Z Z " #b
x2 1 x2
x2 e x2 e
xe dx = + C: xe dx = lim
2 1 b!1 2
1

b2 1 1
e e e b2
= + = ; since lim e = 0:
2 2 2 b!1

X
1
k2
It follows that the integral converges and, by the integral test, so does ke .
k=1

5.

2 2 + sin2 k 3 3 3
2 + sin k 3 =) p3
p
3
p
3
= 4=3 :
k4 + k k4 +k k 4 k

P1 1

4=3
is a convergent p-series (p = 4=3 > 1):
k=1 k

P1 3
Thus 4=3
converges and, by the direct comparison test,
k=1 k

X1
2 + sin2 k
so does the series p
3
.
k=1
k4 + k

2
6.
x2 + 3x A Bx + C
= +
(x + 1) (x2 + 1) x+1 x2 + 1

A(x2 + 1) + (Bx + C) (x + 1) = x2 + 3x:

A + B = 1; B + C = 3 and A + C = 0:

A= 1; B = 2; and C = 1:

Z Z
x2 + 3x 1 2x + 1
dx = + 2 dx
(x + 1) (x2 + 1) x+1 x +1

Z Z Z
1 2x 1
= dx + 2
dx + dx
x+1 x +1 x2 +1

= ln jx + 1j + ln(x2 + 1) + tan 1
x+C